PENGEMBANGAN TEKNOLOGI HURDLE PADA PENGOLAHAN BAKSO MELALUI KOMBINASI BLANCHING DAN PENAMBAHAN EKSTRAK KUNYIT SERTA JAHE - Yuli Witono; Tamtarini Tamtarini; Djoko Ponjto Hardani; Nunik Sulistyowati (JURNAL AGROTEKNOLOGI, 2011)
Meatball processing technology which able to insure it’s safety and prolong the self life was necesarry to be researched. The importance technology to be carried out was development of hurdle technology, i.g. to combine blanching and curcumin and ginger extract addition. The research result showed that combination of blanching and curcumin and ginger extract addition successed to extend the meatball self life, such as: to inhibit microbe growing, to decrease water activity (Aw) and water content. The treatment also influenced on meat ball sensory, to decrease meatball whiteness value and texture. Development of hurdle technology for meatball processing by curcumin and ginger extract of 1,5% and blanching long of 10 minutes resulted the best synergy effect. Keywords: hurdle technology, meatball, blanching, self life, ginger and curcumin